( | 1 100 | × | 15 | ) | ÷ | ( | 1 | + | 1 100 | × | 15 | ) | = | X |
Multiply both sides of the equation by: | ( | 1 | + | 1 100 | × | 15 | ) |
( | 1 100 | × | 15 | ) | = | X | ( | 1 | + | 1 100 | × | 15 | ) |
1 100 | × | 15 | = | X | ( | 1 | + | 1 100 | × | 15 | ) |
1 100 | × | 15 | = | X | × | 1 | + | X | × | 1 100 | × | 15 |
3 20 | = | X | × | 1 | + | X | × | 3 20 |
3 20 | = | 23 20 | X |
- | 23 20 | X | = | - | 3 20 |
3 20 | = | 23 20 | X |
23 20 | X | = | 3 20 |
X | = | 3 20 | ÷ | 23 20 |
= | 3 20 | × | 20 23 |
= | 3 | × | 1 23 |
X | = | 3 23 |
X | = | 0.130435 |